The Limits of Infants' Early Word Learning. Issue 1 (2nd January 2020) - Taxitari, Loukia; Twomey, Katherine E.; Westermann, Gert; Mani, Nivedita
ABSTRACT: In this series of experiments, we tested the limits of young infants' word learning and generalization abilities in light of recent findings reporting sophisticated word learning abilities in the first year of life. Ten-month-old infants were trained with two word-object pairs and tested with either the same or different members of the corresponding categories. In Experiment 1, infants showed successful learning of the word-object associations, when trained and tested with a single exemplar from each category. In Experiment 2, infants were presented with multiple within-category items during training but failed to learn the word-object associations. In Experiment 3, infants were presented with a single exemplar from each category during training, and failed to generalize words to a new category exemplar. However, when infants were trained with items from perceptually and conceptually distinct categories in Experiment 4, they showed weak evidence for generalization of words to novel members of the corresponding categories. It is suggested that word learning in the first year begins as the formation of simple associations between words and objects that become enriched as experience with objects, words and categories accumulates across development.